2022
DOI: 10.3389/fendo.2022.1039919
|View full text |Cite
|
Sign up to set email alerts
|

Association between the RETN -420C/G polymorphism and type 2 diabetes mellitus susceptibility: A meta-analysis of 23 studies

Abstract: BackgroundThe published findings on the link between the resistin (RETN) gene polymorphism and type 2 diabetes mellitus (T2DM) risk are still contradictory. Here, through a meta-analysis, we summarized a more precise evaluation of their connection by synthesizing existing research.MethodsPubMed, Google Scholar, and Web of Science were electronically searched, and all cited sources were manually searched. The heterogeneity of effects was tested and all statistical analyses were performed in Stata 12.0.ResultsA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Among the top three DEPs, RETN belongs to a family of RETN-like molecules . Yao et al suggested that RETN was associated with the immune response and the infiltration of the CD8 + T cells and CD4 + T cells .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the top three DEPs, RETN belongs to a family of RETN-like molecules . Yao et al suggested that RETN was associated with the immune response and the infiltration of the CD8 + T cells and CD4 + T cells .…”
Section: Resultsmentioning
confidence: 99%
“…However, there are no relevant studies about RETN and CELA3A in the drainage fluid. RETN is a family member of mouse resistin-like genes that displays antibacterial activity in the skin against both Gram-positive and Gram-negative bacteria . Moreover, the expression of RETN was significantly associated with immune cell disorders .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The RETN gene is capable of encoding resistin and adipokines in the human body, exhibiting risk associations between resistin and RETN with susceptibility to breast cancer and type 2 diabetes mellitus [30][31]. Furthermore, it has been suggested that polymorphisms in RETN may contribute to an increased susceptibility to colon cancer disease [32].…”
Section: Discussionmentioning
confidence: 99%